MENCIPTAKAN BANK SYARIAH YANG BERPIHAK - Efi Syarifudin (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2013)
Islamic banking has problems in determining its identities which are perceived variedly by the people. The profit sharing system and Islamic legal contract developed in Islamic finance are no longer perceived distinctively because they have been modified adjusting to the trends in common finance system. However, aspects that should have been the spirits (ruh) of Islamic finance can be systematically ruined in the merely profit-oriented infrastructure and business vision. Muslim societies' problems should have been solved by the presence of Islamic banking. One of which is the problem of financial access far the have-nots. This can be constructed as a farm of support which acts as identities and cores of Islamic finance. A number of strategic steps offered in this paper are: 1. The purity of akad (contract) and the creation of togetherness; 2. Making humanity problems as the ultimate orientation, not the accumulation of capital- 3. Making use social modal, creating the environment of support through the development of norms and communal awareness in distributing risk as well as conducting continuous guidance. Through those approaches and steps, Islamic banking is expected to have different identities from those of other finance systems. Therefore, togetherness and familyness (jama'ah wal ukhuwah) can constantly become the ultimate spirits in creating nation's welfare as written in article 33 of the National Constitution (UUD 194 5), and not through the individualistic competitive condition. Keyword: Islamic Bank, Partnership, Intermediation, Empowerment